Assessment of primary production limitation in fish ponds using algal tissue nutrient - Santha, Calista Rohini; Jindal, Vinod Kumar; Illangantileke, Sarath G.; Gupta, Chandra P.; Government of Japan (Bangkok : Asian Institute of Technology, 1986)
Moisture adsorption by paddy results in the formation of fissures leading to a reduction in its head rice yield. In this study, the moisture adsorption characteristics of paddy as affected by initial moisture content (IMC), air temperature (T) a nd relative humidity (RH), and the exposure duration(t) Here determined in order to quantify the reduction in head rice yields during rewetting. Experimental test conditions Here in the following ranges : Paddy initial moisture content, B-15 % Net basis ; air temperature, 20-40°C; air relative humidity, 60-90%; and exposure time, 0 . 5-24 h . A controlled temperature and relative humidity cabinet Has used for rewetting paddy samples Neighing 130 g and placed in Hire-mesh trays. Paddy samples having moisture content more than 13 % Kb after rewetting Here dried to 13 % Kb prior to milling. Samples having moisture content less than 13 % Kb were milled as such. Stepwise multiple regression analysis showed that moisture adsorption in paddy Has affected by IMC, RH, t, T in decreasing order of significance. TKO different approaches Here made to represent the experimental moisture adsorption data. Both models Here found to be adequate to represent the moisture adsorption characteristics of paddy. Rewetting of paddy samples resulted in a reduction in head rice yields , Which was expressed as a ratio of percentage head rice yield of treated sample to that of control sample. Most of t he reduction in head rice yields occurred during the initial few hours of exposure. A relationship between the head yield ratio and t he initial moisture contents of paddy Ha s developed by taking into account the relative contributions of RH, t and T. Such a relationship could be used to quantify the reduction in head rice yields due to moisture adsorption.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1986
Keywords: Fish ponds